Brain Amyloid Index as a Probable Marker Bridging Between Subjective Memory Complaint and Objective Cognitive Performance - Choe, Young Min; Suh, Guk-Hee; Lee, Boung Chul; Choi, Ihn-Geun; Lee, Jun Ho; Kim, Hyun Soo; Hwang, Jaeuk; Kim, Jee Wook (Frontiers in Neuroscience, 2022)
Background: The association between subjective memory complaint (SMC) types, poor objective cognitive performance, and brain A deposition have been poorly understood. We investigated the association between SMC types and objective global cognitive performance, then assessed whether this association is mediated by brain amyloid prediction index (API). Methods: In total, 173 non-demented older adults (63 cognitively normal (CN) and 110 mild cognitive impairment (MCI)) underwent comprehensive clinical assessments. Objective global cognitive performance and brain amyloid index were measured using the total score (TS) of the Consortium to Establish a Registry for Alzheimer’s Disease neuropsychological battery and API, respectively. Four items of SMC from the subjective memory complaints questionnaire (SMCQ) (SMCQ1: feeling of memory problem; SMCQ2: feeling of worse memory than 10 years ago; SMCQ3: feeling of worse memory than others of similar age; or SMCQ4: feeling of difficulty in everyday life) in global memory function were assessed. Results: In non-demented and MCI participants, SMCQ3-positive and SMCQ4-positive groups were associated with decreased TS. In MCI participants, SMCQ3-positive group was associated with increased API and API was associated with decreased TS, but SMCQ4-positive group did not. In addition, the association between SMCQ3-positive group and poor TS disappeared when API was controlled as a covariate, indicating that API has a mediation effect. Conclusions: The present findings suggest that SMC, a feeling of worse memory performance than others in a similar age group, in older adults without dementia is associated with poor objective cognitive performance via increased brain amyloid index.